The Introduction of Sustainable Aviation Fuels—A Discussion of Challenges, Options and Alternatives - Wolfgang Grimme (Aerospace, 2023)
The aviation industry is challenged to reduce its climate impact. The introduction of sustainable aviation fuels (SAF) is, among other policy instruments such as the European Emissions Trading Scheme, an option favored by policymakers in Europe to achieve this objective. These fuels feature substantially reduced carbon life-cycle emissions in comparison to fossil fuels. In Europe, a mandatory quota for the use of sustainable fuels will most likely be introduced, starting in the year 2025. The introduction of a blending mandate by governments and the European Commission is associated with a range of challenges. The purpose of this paper is to discuss the economics of climate change mitigation in aviation and the role SAFs can play. The economic issues associated with the introduction of SAFs are analyzed, with a particular focus on the European Commission’s proposal for a blending mandate. Several suggestions for improvement are discussed. Furthermore, alternatives to SAFs are presented and evaluated.